Reliability of Sonoelastography Measurement of Tongue Muscles and Its Application on Obstructive Sleep Apnea - Chu, Cheng An; Chen, Yunn-Jy; Chang, Ke-Vin; Wu, Wei-Ting; Özçakar, Levent (Frontiers in Physiology, 2021)
Few studies have explored the feasibility of shear-wave ultrasound elastography (SWUE) for evaluating the upper airways of patients with obstructive sleep apnea (OSA). This study aimed to establish a reliable SWUE protocol for evaluating tongue muscle elasticity and its feasibility and utility in differentiating patients with OSA. Inter-rater and intra-rater reliability of SWUE measurements were tested using intraclass correlation coefficients. Submental ultrasound was used to measure tongue thickness and stiffness. Association between the ultrasound measurements and presence of OSA was analyzed using multivariate logistic regression. One-way analysis of variance was used to examine if the values of the ultrasound parameters varied among patients with different severities of OSA. Overall, 37 healthy subjects and 32 patients with OSA were recruited. The intraclass correlation coefficients of intra- and inter-rater reliability for SWUE for tongue stiffness ranged from 0.84 to 0.90. After adjusting for age, sex, neck circumference and body mass index, the risk for OSA was positively associated with tongue thickness (odds ratio 1.16 [95% confidence interval 1.01–1.32]) and negatively associated with coronal imaging of tongue muscle stiffness (odds ratio 0.72 [95% confidence interval 0.54–0.95]). There were no significant differences in tongue stiffness among OSA patients with varying disease severity. SWUE provided a reliable evaluation of tongue muscle stiffness, which appeared to be softer in patients with OSA. Future longitudinal studies are necessary to investigate the relationship between tongue softening and OSA, as well as response to treatment.